Screening For Breast Cancer Amongst High-Risk Population At A Tertiary Care Hospital from Rawalpindi - Jan, Maria Mir; Rifat Naqvi, Syeda Qamar; Azam, Zaini; Gul, Shandana; Tariq, Maham; Zaman, Said (Pakistan Armed Forces Medical Journal, 2026)
Objective: To identify high-risk for breast cancer population amongst entitled females and to detect breast disease/cancer by screening tests (mammography or sonomammography) in the high-risk/symptomatic group.Study Design: Cross-sectional study.Place and Duration of Study: Breast Surgery Department, Combined Military Hospital Rawalpindi, Pakistan, from Sep 2022 to Feb 2023.Methodology: In 3 phases, questionnaire based on the Gail model (translated to Urdu) were sent to entitled female Rawalpindi area and its periphery. A “Yes” response indicated high-risk/symptomatic females, who were then called to the department for screening. Bilateral (B/L) Sonomammography in women less than 40 years and B/L mammography for over 40 years females was done.Results: Out of 2000 questionnaires sent, 1418(70.9%) responded. Nine hundred and twenty-two (65.0%) of these were below 40 years of age.  Seventy-four high-risk cases underwent 41 sonomammographies and 33 mammograms. Twenty-four (32.0%) of results were unremarkable, 23(31.0%) benign breast lesions, 2 ductal carcinoma in-situ (DCIS) requiring excision. Fifteen (20.0%) newly diagnosed breast cancers were detected. Pre-diagnosed cases of 9(12.0%) breast cancers were also checked, including a BRCA1 patient. The predominant stage for new cancers was Stage-II (46.0%), while it was III (44.0%) for old cases. Total of 24 (32.0%) breast cancer cases from high-risk screened population accounted for 1.8% of the studied group.Conclusion: The study emphasized the need for screening program in Pakistan, and indicated that more young females in spite of no risk factors developed breast cancer.